Broadening horizons: the multifaceted role of ferroptosis in breast cancer - Ge, Anqi; Xiang, Wang; Li, Yan; Zhao, Da; Chen, Junpeng; Daga, Pawan; Dai, Charles C.; Yang, Kailin; Yan, Yexing; Hao, Moujia; Zhang, Bolin; Xiao, Wei (Frontiers in Immunology, 2024)
Breast cancer poses a serious threat to women’s health globally. Current radiotherapy and chemotherapy regimens can induce drug-resistance effects in cancer tissues, such as anti-apoptosis, anti-pyroptosis, and anti-necroptosis, leading to poor clinical outcomes in the treatment of breast cancer. Ferroptosis is a novel programmed cell death modality characterized by iron overload, excessive generation of reactive oxygen species, and membrane lipid peroxidation. The occurrence of ferroptosis results from the imbalance between intracellular peroxidation mechanisms (executive system) and antioxidant mechanisms (defensive system), specifically involving iron metabolism pathways, amino acid metabolism pathways, and lipid metabolism pathways. In recent years, it has been found that ferroptosis is associated with the progression of various diseases, including tumors, hypertension, diabetes, and Alzheimer’s disease. Studies have confirmed that triggering ferroptosis in breast cancer cells can significantly inhibit cancer cell proliferation and invasion, and improve cancer cell sensitivity to radiotherapy and chemotherapy, making induction of ferroptosis a potential strategy for the treatment of breast cancer. This paper reviews the development of the concept of ferroptosis, the mechanisms of ferroptosis (including signaling pathways such as GSH-GPX4, FSP1-CoQ1, DHODH-CoQ10, and GCH1-BH4) in breast cancer disease, the latest research progress, and summarizes the research on ferroptosis in breast cancer disease within the framework of metabolism, reactive oxygen biology, and iron biology. The key regulatory factors and mechanisms of ferroptosis in breast cancer disease, as well as important concepts and significant open questions in the field of ferroptosis and related natural compounds, are introduced. It is hoped that future research will make further breakthroughs in the regulatory mechanisms of ferroptosis and the use of ferroptosis in treating breast cancer cells. Meanwhile, natural compounds may also become a new direction for potential drug development targeting ferroptosis in breast cancer treatment. This provides a theoretical basis and opens up a new pathway for research and the development of drugs for the prevention and treatment of breast cancer.